(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Funded by the U.S. Department of Energy’s Water Power Technologies Office (DOE WPTO), and launched in 2019, the Portal and Repository for Information on Marine Renewable Energy (PRIMRE) (https://primre.org) is an interconnected system of knowledge hubs that provide access to data, information, and other resources for the marine energy community. Each knowledge hub has its own unique identity, structure, and purpose: • MHKDR (https://mhkdr.openei.org/)is the Marine and Hydrokinetic Data Repository for all data collected by marine energy research and development projects funded by DOE. • Tethys (https://tethys.pnnl.gov/) hosts documents, educational resources, and online tools on the environmental effects of marine and wind energy development. • Tethys Engineering (https://tethys-engineering.pnnl.gov/) hosts documents on the technical and engineering aspects of marine energy research and development. • Marine Energy Projects Database (https://primre.org/Projects_Database) contains up-to-date information on marine energy projects, devices, companies/organizations, and test sites around the world. • Marine Energy Software (https://software.primre.org/) is a collection of open-source and commercial software relevant to marine energy research and development. • Marine Energy Atlas (https://maps.nrel.gov/marine-energy-atlas/) is a geospatial mapping tool that allows users to visualize, analyze, and download geospatial datasets relevant to marine energy resources. • Telesto (https://primre.org/Telesto) hosts information about the development life cycle of marine energy, including planning, designing, building, testing, deploying, and decommissioning, as well as information on lessons learned, metrics, economics, standards, and compliance. By serving as a centralized access point, PRIMRE provides broad access to marine energy data and information across all seven knowledge hubs. Furthermore, PRIMRE’s centralized search (https://openei.org/wiki/PRIMRE/Search) allows users to easily search, filter, and find content within the PRIMRE universe. The Ask PRIMRE generative AI research assistant (https://openei.org/wiki/PRIMRE#askModal) enables users to get quick answers to contextual questions and guides them to insights beyond simple keyword searches. Additional features on PRIMRE include an events calendar, archived webinars, educational content, a biweekly newsletter, a free use photo library, a variety of online tools, and links to external resources. Altogether, PRIMRE provides centralized access to marine energy data and information – content that would otherwise be inaccessible and unusable by the public. Through its continued funding by DOE WPTO and support by the Sandia National Laboratories, National Renewable Energy Laboratory, and Pacific Northwest National Laboratory team, PRIMRE’s content is curated and maintained by a muti-lab team of experts with diverse backgrounds. Collectively, the multidisciplinary team has decades of experience in marine energy and data and information system management and is building trust with the user community. By focusing on user needs and experience in the design of PRIMRE and its Knowledge Hubs, PRIMRE has established itself as the primary access point for marine energy data and information in the United States. PRIMRE is also a leader in the data sharing space and connects with other ocean energy data systems around the world through Application Programming Interface (API) exchanges to enable data sharing for universal and transparent access. As the marine energy industry expands globally, the PRIMRE team is exploring this area of opportunity and looking to share lessons learned for data and information sharing more broadly.